Exploração e análise de dados coletados pelo sistema integrado de monitoramento ambiental utilizando técnicas de visual analytics - Carmo, Alisson Fernando Coelho do [UNESP] (2015)
The man intervention process in the environment has huge influence on the changes that occur in it. It is important monitoring the features and phenomena involved in this process to identify, interpret and control such changes. The identification of fast varying phenomena requires a high temporal resolution dataset, what can constrain remote sensing utilization, due to insufficient data collection rate. On the other hand, the analysis of changes caused by slow processes is done from long historical records, which come from a periodic data acquisition during a long period of time, which can make traditional technique, such as fieldwork campaings, an inappropriate approach due to the rate of collection. The technological development has been raising the use of automated sensors to collect data, such as the Environmental Monitoring Integrated System (Sistema Integrado de Monitoramento Ambiental, SIMA) that is the source of dataset used in this project. In the SIMA project, a set of platforms, which are capable of collecting air and water attributes automatically and periodically, are anchored to hydroelectric power dams. However, the dataset may be incomplete because of problems in one or more of the following phases: acquisition, transmission or storing. Due to huge amount of multivariate temporal data and the lack of dataset in some cases, the visual and interactive exploration can support the task of its characterization. In this project, Information Visualization techniques are applied to dataset characterization process, searching for features that may affect the quality of the associated phenomena analysis. Standards for data modelling and availability, aiming the flexibility for application development and interoperability among resources, have also been investigated...